Male reproductive system of the red brocade hermit crab Dardanus insignis (Diogenidae) and its relationship to other family members - Buranelli, Raquel C.; Zara, Fernando J. [UNESP]; Mantelatto, Fernando L. [UNESP] (Springer, 2014)
The reproductive system of hermit crabs shows species-specific morphology, which can be used in phylogenetic analysis. Here, we describe the male reproductive system of the hermit crab Dardanus insignis, including morphological and biometric analyses of the spermatophore, the gonopore, and sperm ultrastructure. The morphological analyses were based on 15 selected specimens and carried out by means of light and electron microscopy. Our results indicate a reproductive system composed of lobular testes attached to a simple straight vas deferens connected to the exterior via ventral gonopores. The gonopores are ovoid, surrounded by dense serrulate setae, and covered by a membranous operculum. The spermatophores exhibit a tripartite structure, with an elongate ovoid ampulla, a long narrow stalk, and a proximal foot. The spermatozoal ultrastructure shows three main regions: an ovoid-oblong acrosomal vesicle, a nucleus, and cytoplasm with three armlike extensions. Some of these characteristics can also be found in other species of Diogenidae within the genus Dardanus and in members of Coenobitidae, a closely related family. The available information on spermatophore and spermatozoal structure may indicate a closer similarity between the genus Dardanus and the Coenobitidae, compared with other members of Diogenidae.
Keywords: Decapoda; Gonopore; Reproduction; Spermatophore; Spermiotaxonomy